Knowledge, skills and leadership key characteristics of administrators - Nor Salwana, Mohammad Idris (2021)
PEKAN, 2 August 2021 - The administrators of Universiti Malaysia Pahang (UMP) are encouraged to embody three important characteristics, namely knowledge, skills and leadership in administration and always open their minds in fulfilling tasks and commitments.